HUBUNGAN ANTARA KEBERMAKNAAN KERJA DENGAN KOMITMEN ORGANISASI - Abraham Irianto; Berta Esti Ari Prasetya (PSIKOLOGI KONSELING, 2021)
This research aimed to knew the relationship between meaningful work and organizational commitment. The participants of this study consisted of 52 partisipants. The hypothesis in this research was the existence of a positive significant relation between meaningful work and organizational commitment. Measurement instruments in this research was a Work and Meaning Inventory by Steger, Dik, and Duffy (2012) and Organizational Commitment Questionnaire by Meyer and Allen (1990). Data analysis technique used Product Moment Correlation by Karl Pearson and helped by SPSS ver 16.00 for Windows. The result in this research found there was a positive and significance correlation between meaningful work and organizational commitment that r = 0,442 with a significance of p = 0,001 (P<0,005) which meant with higher meaningful work, the organizatinal commitment would be high. Otherwise with lower meaningful work, organizational commitment would be low.